Does composition matter? Wage inequality and the demographic and educational structure of the labor force in Gemany - Marcus Klemm; Benjamin Weigert (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2014)
This paper addresses the importance of compositional changes in the labor force for the development of the wage distribution. Demographic change and higher educational attainment imply a shift toward employees with more experience and/or better education. These groups are characterized by higher relative wages as well as higher within-group wage inequality. Mechanically, these compositional shifts entail a rise in wage inequality. We demonstrate this mechanism theoretically and present empirical evidence using data of the German Socio-Economic Panel from the mid 1990's to 2012. Accounting for the parallel changes in the age structure and the educational background of the labor force, the compositional effects alone can explain up to one quarter of the observed increase in aggregate wage inequality.
Keywords: J31; D31; J11; 330; wage structure; inequality decomposition; demographic change; population aging; education; skills